Pengenalan Konsep Eko-eduwisata Mangrove di Desa Wisata Pengudang Kabupaten Bintan - Rika Anggraini; Agung Dhamar Syakti; Fadhliyah Idris; Try Febrianto; Harish Wirayuhanto; Mario Putra Suhana (LPPM Universitas Trunojoyo Madura, 2022)
Mangrove ecosystems have functions and benefits that are quite important both physically and biologically. Mangroves can act as natural coastal protectors from damage due to abrasion and large waves and also provide shelter for associated biota. Development of a mangrove ecosystem that can be developed into a tourism area and an environmental-based education center. Pengudang Village has the potential to be developed into a mangrove ecotourism area with its resources and biodiversity. Development into a mangrove ecotourism area is constrained by public understanding of the types of mangroves, benefits and associated biota in the mangrove ecosystem of Pengudang Village. Community service activities carried out aim to provide understanding to the Pengudang Village community about the potential and types of mangrove resources and associated biota. The activity process begins with a survey of the potential of the mangrove ecosystem including recording, identification, and classification of mangrove species. The introduction and socialization of the condition of the man-grove ecosystem was carried out to the coastal community of Pengudang Village. From the results of field identification, it was found that the mangrove condition of Pengudang Village is in good condition with a dense density. Associated biota in mangrove ecosystems vary from gastropods to mammals. The identification results are disseminated to the Pengudang Village community.